Integrating of the seahorse Hippocampus reidi in multi-trophic organic farms of oysters and shrimp: Effects of density and diet: Integración del caballito de mar Hippocampus reidi en granjas de cultivo multitrófico orgánico de ostras y camarones: Efectos de la densidad y la dieta - Carvalho, Thiago L.; Cacho, Julio Cesar S.; Souza, Rafaela S.; Morais, Jefferson A.; Wandeness, Adriane; Carlos, Marco Tulio L.; Wainberg, Alexandre A.; Souza-Santos, Lília P.; Ribeiro, Felipe A. S. (Revista de Biología Marina y Oceanografía, 2019)
The goal of this study was to demonstrate the feasibility of culturing the seahorse Hippocampus reidi in an organic integrated multi-trophic aquaculture farm that produces the oyster Crassostrea brasiliana and the shrimp Litopenaeus vannamei. Experiments were conducted to evaluate the effects stocking density and food (natural zooplankton, Artemia nauplii, or both) for the juvenile I, which are fish from 1 to 15 days after birth. Stocking density effect was studied on growth and survival of juveniles II from 30 days to commercial size in net cages. Survival of the juvenile I was not affected by stocking densities from 2 to 5 ind L-1 and was greater than 70% in all treatments. Seahorse length, however, was inversely related to stocking density. Both treatments with wild zooplankton promoted higher seahorse survival and growth than diet composed exclusively by Artemia sp. during the first 15 days of life. Juvenile II growth decreased with stocking density from 5 to 40 ind m-3 but survival was not affected by it. The total benefit and proportion of colored animals increased significantly with stocking density. The present study confirms the technical feasibility of organic multi-trophic seahorse production in net cages. Even at the highest density tested the seahorses grew well and could generate high profits.